Identifying the General Equilibrium Effects of Narcotics Enforcement - Zachary Porreca (Global Labor Organization (GLO), 2024)
I analyze the demand side impacts of a supply side intervention into the market for illegal drugs in what has been described as America's largest open air drug market. Beginning in 2018, the Pennsylvania Attorney General's office and the Philadelphia Police Department engaged in an ambitious effort to shut down the drug market in Philadelphia's Kensington neighborhood. The intervention involved increased police presence in the targeted area alongside a series of targeted "kingpin" sweeps which were intended to remove the most pervasive operators from the market. I employ highly granular Safegraph cell phone location data to track changes in traffic flows between census block groups, observing that the initiative led to sizable and persistent reductions in traffic flows to the target area. Additionally, in contrast to substitution effects observed in other work, I observe that the initiative led to reductions in traffic flows to other regional drug markets and large declines in overdose mortality in the Philadelphia metropolitan area as a whole, suggesting a genuine reduction in the demand for illegal narcotics. With a combination of theory and empirics, I argue that this reduction in regional demand is able to be achieved due to the initiative disrupting a supply-chain that data indicates flows from the target area outwards to smaller satellite markets. Together this all suggests that, despite the inelastic demand for narcotics, regionally linked markets can be impacted broadly by location specific interventions.
Keywords: K42; R12; I19; H00; 330; Drug Markets; Supply Side Enforcement; Cell Phone Locations; Kensington